Transformasi analisis konfigurasi desain smart office desk untuk kebutuhan work from home - Irna Arlianti; Amila Sofiah; Hertina Susandari (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2023)
The work from home concept has become a common work system to reduce the rate of spread of COVID-19 cases. The adjustment of the portion of working in the office only below 50% in the next few years. Unfortunately, the impact of working from home is the flexibility of working time. There is no dividing wall between work time and personal time. Increased workloads and work delays often occur which ultimately affect the performance of workers. The work desk design development could be alternative solution. Referring to the trend of furniture design in the next few years, smart furniture design is becoming a trend that is in demand and needed to improve the quality of life. Smart furniture includes the application of intelligent systems / controllers to furniture designs in the form of sensors and actuators that are tailored to user needs. Research was conducted on the configuration analysis of smart office desk designs for the needs of working at home. The results are recommendations for the layout of user detector on the desk, the process of integrating the desk and the user detector, the final design, the design requirements and objectives in the development of a smart office desk.